PEMAHAMAN MISDINAR TERHADAP PERAYAAN EKARISTI DI STASI SANTO PIUS X PULAU SICANANG PAROKI SANTO KONRAD MARTUBUNG - Arnoldus Rudolfo Situmorang; Mimpin Sembiring (Bahasa Indonesia, 2026)
This study examines the understanding of altar servers regarding the Eucharistic Celebration at St. Pius X Station, Sicanang Island, Santo Konrad Martubung Parish. The background of this research is rooted in the crucial role of altar servers in supporting the solemnity and order of the liturgy, while in practice many of them demonstrate limited comprehension of the spiritual, theological, and symbolic dimensions of the Eucharist. The study aims to analyze how altar servers understand their role and participation in the Eucharistic liturgy. A descriptive qualitative approach was employed, with data collected through participatory observation, in-depth interviews, and documentation. The findings reveal that the altar servers’ understanding tends to be predominantly technical rather than spiritual. Their service is often carried out as a routine activity, with minimal awareness of liturgical symbolism and the deeper meaning of Eucharistic celebration. In addition, motivation to serve is frequently influenced by peer encouragement rather than personal vocation. The research highlights the need for continuous and holistic formation that integrates liturgical knowledge, spiritual growth, and character development. Such formation is essential to foster altar servers who are not only competent in carrying out technical tasks at the altar but also spiritually mature, responsible, and conscious of the sacred mystery they serve in the life of the Church.